Effect of Molybdenum on the Corrosion Behavior of High-Entropy Alloys CoCrFeNi2 and CoCrFeNi2Mo0.25 under Sodium Chloride Aqueous Conditions - Alvaro A. Rodriguez; Joseph H. Tylczak; Michael C. Gao; Paul D. Jablonski; Martin Detrois; Margaret Ziomek-Moroz; Jeffrey A. Hawk (Advances in Materials Science and Engineering)
The corrosion behavior of high-entropy alloys (HEAs) CoCrFeNi2 and CoCrFeNi2Mo0.25 was investigated in 3.5 wt. percent sodium chloride (NaCl) at 25°C by electrochemical methods. Their corrosion parameters were compared to those of HASTELLOY® C-276 (UNS N10276) and stainless steel 316L (UNS 31600) to assess the suitability of HEAs for potential industrial applications in NaCl simulating seawater type environments. The corrosion rates were calculated using corrosion current determined from electrochemical experiments for each of the alloys. In addition, potentiodynamic polarization measurements can indicate active, passive, and transpassive behavior of the metal as well as potential susceptibility to pitting corrosion. Cyclic voltammetry (CV) can confirm the alloy susceptibility to pitting corrosion. Electrochemical impedance spectroscopy (EIS) elucidates the corrosion mechanism under studied conditions. The results of the electrochemical experiments and scanning electron microscopy (SEM) analyses of the corroded surfaces revealed general corrosion on alloy CoCrFeNi2Mo0.25 and HASTELLOY C-276 and pitting corrosion on alloy CoCrFeNi2 and stainless steel 316L.